Power-Aware Architecting for data-dominated applications - Ditzel, Maarten; Otten, R.H; Serdijn, Wouter A. (Springer Netherlands : Imprint: Springer, 2007)
The task of the system architect is to take the correct early decisions despite the uncertainties. Power-Aware Architecting provides a systematic way to support the system architect in this job. Therefore, an iterative system-level design approach is defined where iterations are based on fast and accurate estimations or predictions of area, performance and energy consumption. This method is illustrated with a concrete real life example of multi-carrier communication. This book is the result of a Ph.D. thesis, which is part of the UbiCom project at Delft University of Technology. I strongly recommend it to any engineer, expert or specialist, who is interested in designing embedded systems-on-a-chip. Jef van Meerbergen Professor Eindhoven University of Technology Fellow Philips Research Eindhoven.